Psychogeriatrics : report of a WHO Scientific Group. - WHO Scientific Group on Psychogeriatrics (Geneva : World Health Organization, 1972)
Hoe zit het met de psychogeriatrie?
Keywords: Geriatric psychiatry; Geriatric psychiatry